TheDadLab : 50 awesome science projects for parents and kids - Urban, Sergei (TarcherPerigee, 2019)
"With more than 3 million fans, TheDadLab has become an online sensation, with weekly videos of fun and easy science experiments that parents can do with their kids. These simple projects use materials found around the house, making it easier than ever for busy moms and dads to not only spend more quality time with their children, but also get them interested in science and technology. In this mind-blowing book, Sergei Urban takes the challenge off-screen with fifty step-by-step projects, including some that he has never shared online before. Each activity will go beyond the videos, featuring detailed explanations to simplify scientific concepts for parents and help answer the hows and whys of their curious children. Learn how to: explore new fun ways to paint; make slime with only two ingredients; defy gravity with a ping-pong ball; produce your own electricity, and more! With TheDadLab, parents everywhere will have an easy solution to the dreaded "I'm bored" complaint right at their fingertips!"--Amazon.com.